Development of Items for Measuring the Competency of Registered Dietitian Students before Graduation - Nagahata, Tomomi; Nakabou, Yukihiro; Yoshiike, Nobuo; Akamatsu, Rie; Komatsu, Tatsushi; Date, Chigusa; Nara, Nobuo; Nagai, Narumi; Ishida, Hiromi (Eiyōgaku zasshi, 2012)
Objective: The purpose of this study was to develop items for measuring the competency of registered dietitian students before they graduated from their training institution, by obtaining information regarding practical expertise and skill requirements. Methods: We reviewed the literature regarding domestic and international competency models and prepared a Japanese registered dietitian's competency model, which had a 3-layer structure: A, elementary; B, general; and C, occupational. The practical expertise required before graduation was determined as follows: For the primary data extraction, an expert panel from each occupational field (i.e., clinical nutrition, public health nutrition, and food service management) determined the competency items relevant to layers A-C of the model. For the second data extraction, cards containing all the primary extraction items were prepared and reclassified into layers A-C by eliminating and integrating concepts and content common to each occupational area. For the final data extraction, items that were particularly important were extracted from the second extraction items, which were needed before graduation, and adopted as competency measurement items. Results: We extracted 582 items during the primary data extraction and 124 items during the second data extraction. On final extraction, 40 items were adopted for measuring the competency of registered dietitian students before graduation. The items were divided into the following categories: A, elementary competency (4 items: values, self-confidence, motivation, and attitude); B, general competency (29 items: practical expertise was considered as a particularly important item for judging the registered dietitian's performance); and C, occupational competency (7 items: a minimum level of specialized practical experience in public nutrition, clinical nutrition, and in food service fields was considered particularly important). Conclusion: We adopted a Japanese registered dietitian's competency model and developed items for measuring the competency of registered dietitian students before graduation by using expert panels. In future studies, we will evaluate the competency level of senior students and use this competency model to analyze the factors required for achieving improved professional performance.